Strategy of medical and psychological assistance in the work of a medical psychologist with oncological patients - Stanovskyi, Богдан (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of a distance report to the IV scientific-practical conference with international participation "Psychosomatic Medicine: Science and Practice". The following is devoted to the strategy of medical and psychological care in the work of a psychologist with cancer patients.